Evaluating GSMaP for Effective Rainfall Estimation in the Bengawan Solo Hulu Watershed Region - Dicky Lutfi Makhfudzi; Cahyono Ikhsan; Rintis Hadiani (Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Nahdlatul Wathan Mataram, 2026)
Effective rainfall is an important parameter in water resource management because it represents the portion of rainfall that can be reliably utilized to meet crop water requirements. However, its estimation generally requires long-term rainfall observations, which are often limited in many regions. Satellite precipitation products offer an alternative rainfall data source, but their applicability for effective rainfall estimation remains insufficiently explored. This study evaluates the capability of Global Satellite Mapping of Precipitation (GSMaP) for estimating effective rainfall using observations from five rainfall stations around the Bengawan Solo Hulu Watershed Region, Indonesia, during 2015–2024. Daily GSMaP rainfall was compared with ground observations and used to calculate dependable rainfall with an 80% exceedance probability (R80) and effective rainfall for rice cultivation (Re). Performance was evaluated using CC, PBIAS, NSE, and MAE. The results showed that GSMaP had moderate performance for daily rainfall, with average CC and NSE values of 0.54 and 0.07. Performance improved at semi-monthly and monthly scales, with CC values of 0.83 and 0.87, respectively. GSMaP also represented the seasonal pattern of dependable rainfall. Effective rainfall estimated from GSMaP showed better agreement with observation-based estimates, with CC reaching 0.92 and NSE exceeding 0.66. These findings indicate that GSMaP has potential as an alternative data source for effective rainfall estimation in regions with limited rainfall observations